Концепт "перемога" в російській та англійській лінгвокультурах - Росовецький, Станіслав Станіславович (Київський національний університет імені Тараса Шевченка, 2016)
У статті аналізуються розбіжності у сприйнятті концепту "перемога" в російській та англійській лінгвокультурах при залученні широкого фразеологічного матеріалу двох мов та за допомогою асоціативного експерименту.

Differences in concepts with phraseological material comparison and associative experiment. The way concepts are different from the point of view of phraseological material, compared in English and Russian lingvocultures, and brand new associative experiment, illuminating concepts embodiments in native speaker’s minds of both languages. This two perspectives allow to make a conclusion about real differences in the way Russian- and English-speakers understand victory.
Concept "victory" in russian and english lingvocultures
Keywords: концепт; перемога; асоціативний експеримент; фразеологія; концептологія; порівняльна культурологія; concept; victory; associative experiment; phraseology; conceptology; comparative culturology